Microtubule stabilization promotes the synthesis of type 2 collagen in nucleus pulposus cell by activating hippo-yap pathway - Zhang, Xin; Shu, Shibin; Feng, Zhenhua; Qiu, Yong; Bao, Hongda; Zhu, Zezhang (Frontiers in Pharmacology, 2023)
Intervertebral disc degeneration (IDD) is the cardinal pathological mechanism that underlies low back pain. Mechanical stress of the intervertebral disc may result in a change in nucleus pulposus (NP) cells state, matrix degradation, and degeneration of the disc. Microtubules, which are components of the cytoskeleton, are involved in driving or regulating signal pathways, which sense and transmit mechano-transduction. Microtubule and the related proteins play an important role in the development of many diseases, while little is known about the role of microtubules in nucleus pulposus cells. Researchers have found that type II collagen (COL2) expression is promoted by microtubule stabilization in synovial mesenchymal stem cells. In this study, we demonstrated that microtubule stabilization promotes the expression of COL2 in nucleus pulposus cells. Stabilized microtubules stimulating Hippo signaling pathway, inhibiting YAP protein expression and activity. In addition, microtubules stabilization promotes the expression of COL2 and alleviates disc degeneration in rats. In summary, our study for the first time, identifies microtubule as a promising therapeutic target for IDD, up-regulating the synthesis of COL2 via Hippo-Yap pathway. Our findings may provide new insights into the etiologies and pathology for IDD, further, targeting of microtubule acetylation may be an effective strategy for the treatment of IDD.